Sequential solid entrapment and in situ electrolytic alkaline hydrolysis facilitated reagent-free bioelectrochemical treatment of particulate-rich municipal wastewater - Khalfbadam, H.; Ginige, M.; Sarukkalige, Priyantha Ranjan; Kayaalp, A.; Cheng, K. (IWA Publishing, 2017)
© 2017 Elsevier LtdWe introduce here a novel process for the treatment of particulate-rich wastewater. A two-stage combined treatment process, consisting of an electrolysis filter and a bioelectrochemical system (BES) configuration was designed and evaluated to remove particulate and soluble organic matter from municipal wastewater. The system was designed such that the electrolysis step was used as a filter, enabling physical removal and in situ alkaline hydrolysis of the entrapped particulate matter. The alkaline effluent enriched with the hydrolysed soluble compounds (soluble chemical oxygen demand, SCOD) was subsequently loaded into the BES for removal via bioanodic oxidation. The coupled system was continuously operated with a primary sedimentation tank effluent (suspended solids (SS) ~200 mg/L) for over 160 days, during which SCOD and total COD (TCOD), SS removal and current production were evaluated. With no sign of clogging the process was able to capture near 100% of the SS loaded. A high Coulombic efficiency (CE) of 93% (based on overall TCOD removed) was achieved. The results also suggest that the SCOD-laden alkaline liquor from the electrolysis step compensated for the acidification in the bioanode and a final effluent containing low COD with neutral pH was achieved. Overall, since the system can effectively entrap, in situ hydrolyse and oxidise organic matter without external dosing of chemicals for pH control, it has desirable features for practical application.